Association of frailty with cognitive impairment and functional disability in older adults with affective disorders: a brief research report - Monteiro, Ariane M.; Borges, Marcus K. (Frontiers in Psychiatry, 2023)
The Clinical-Functional Vulnerability Index (IVCF-20) is a validated multidimensional instrument that has been used in Brazil to evaluate functional disability in frail older adults. The main aim of this study was to assess frailty using this novel screening tool. In addition, to investigate whether frailty was associated with cognitive impairment and functional disability in older adults with affective disorders. Methods: Participants included were over 60 years old, with affective disorders (depressive or anxiety disorders), from two specialized outpatient clinics. The sample was comprised of 46 patients (30% of a total from 153). The following instruments were applied: Clock Drawing Test (CDT), Mini Mental State Examination (MMSE); Verbal Fluency Test (VFT); Pfeffer Questionnaire or Functional Assessment Questionnaire (FAQ); Katz Index; Geriatric Depression Scale (GDS-15); Geriatric Anxiety Inventory (GAI), and IVCF-20 as well as sociodemographic and clinical questionnaires. The association between the variables of interest was estimated using Spearman correlation. Results: This study found a negative correlation between frailty and cognitive decline (MMSE) (rs=-0.58; p<0.001); (VFT) (rs=-0.60; p<0.001); (CDT) (rs=-0.47; p=0.001) and a positive correlation between frailty and depressive symptoms (GDS-15) (rs=0.34; p=0.019) as well as disability for IADLs (FAQ) (rs=0.69; p<0.001). However, there was no statistical difference in the association between frailty and anxiety symptoms (GAI) (rs=0.24; p=0.103) or disability for BADLs (Katz) (rs=-0.02; p=0.895). Discussion: Our data support that the associations between frailty, cognitive and functional disability are prevalent issues in Psychogeriatrics. Assessing frailty in a multidimensional context is essential using a rapid assessment frailty tool in clinical practice.